Naturally Coloured Corriedale – Historical, racial characteristics and the origin of colors (Research, Society and Development, 2020)
The selection caused by the domestication process made changes in the sheep phenotype, leading to the prevalence of white biotypes in most breeds. However, the population's awareness of the sustainability of production systems and the importance of environmental preservation has driven the search for products with reduced environmental impact, encouraging the selection of naturally pigmented sheep. The present literature review aimed to gather information about the breed Corriedale and the factors that cause the coloration of the animals, as well as their reflections on the products coming from them. The colorful Corriedale originated in New Zealand and is one of the most common breeds among the naturally colored ones. Wool pigmentation is usually caused by the occurrence of a recessive variation of genes. Large numbers of genes coordinate the presence, distribution and biochemical activity of melanocytes, which synthesize the pigments that determine the color of the animals. Skins and pigmented wools have alternative uses, recognized by the non-need for industrial processing and the peculiar characteristics, which allow the obtaining of singular products. It is concluded that the creation of colored sheep presents a tendency of expansion, based on the ecological approach and non-aggression to nature, with potential of adding value to the products.